Complementing Farmers' Genetic Knowledge Farmer Breeding Workshop in Turipaná, Colombia - Saad, N; Hernández, L.A.; Morante, N (CGIAR System Organization, 2001)
This workshop explored the feasibility and methods for complementing farmer experts' knowledge and skills in the enhancement and conservation of agrobiodiversity.